FLAVONOIDS AND THEIR ANTIOXIDATIVE, ANTIMICROBIAL AND ANTI-TUMOR PROPERTIES AND CAPACITY: FLAVONOIDS - PROPERTIES AND CAPACITY - Ilic Todorovic, Violeta; Piric (PONS - medicinski časopis, 2023)
The goal of the paper is to analyze the results of the research and present the general characteristics of flavonoids, including their biosynthetic pathway and peculiarities of secondary metabolism, through a review of available published works. Also, the work follows the antioxidant, antimicrobial and antitumor properties, and capacity of flavonoids. Flavonoids including flavones, isoflavones and anthocyanidins are formed by the condensation of phenylpropanoids with the participation of three molecules of malonyl coenzyme A. Flavonoid synthesis begins with phenylalanine, using the enzyme phenylalanine ammonium lyase (PAL) which catalyzes the release of phenylalanine and phenylalanine. Various experimental studies have shown that phenylalanine is a precursor of a large product of the secondary metabolism of phenolic compounds. The professional literature points out that o-dihydroxylation of the B-ring contributes to the antioxidant activity of flavonoids, while its antimicrobial properties are determined by the presence of (+) - catechin and quercetin against gram-positive and gram-negative bacteria. When it comes to antitumor properties, antioxidant activity, regulation of p53 protein, inhibition of protein kinase activity and apoptosis have an impact.